Revisão sistemática do complexo de espécie Trichomycterus brasiliensis (Siluriformes: Trichomycteridae) - Vianna, Maria Anaïs Barbosa Segadas (2000)
Trichomycterus Valenciennes is the most representative genus in the family Trichomycteridae, with more than 100 species described (de Pinna, 1992), but characterized by absence of unique diagnostic features. Therefore, there is no doubt, the genus is non-monophyletic ( de Pinna 1998), to constitute the most problem in the family, and originating the urgent need for news revisions papers. There are a extraordinary diversity of Trichomycterus in the mountain streams of southeast Brazil (Costa,1992) inhabiting hydrological basins of the river São Francisco, Paraíba, Grande, Doce, and small coast basins. The present paper describes a monophyletic assemblage including Trichomycterus brasiliensis Lütken, T mimonha Costa, T mirissumba Costa, T vermiculatus (Eigenmann), T candidus (Ribeiro) n. comb. and five new species, herein denominated as Trichomycterus brasiliensis species-group. Its relationships can be establish on the base in four derived characters.